Effect of water imbibition on uniaxial compression strength of sandstone. (March 2020) - Liu, Honglei; Zhu, Wancheng; Yu, Yongjun; Xu, Tao; Li, Rufei; Liu, Xige
Abstract: Rock is a typical porous and heterogeneous geological medium, and water imbibition has a great influence on its mechanical properties. The degree of water imbibition in rock heavily depends on the internal fissures of rock and the soaking time. Here, sandstone specimens were soaked in a red ink solution for different amounts of time, and then cross sections were photographed to obtain RGB images of the water distribution in the rock. Next, the correlation between the water distribution in the rock specimens and the RGB values of the images was established to characterize the water distribution in the sandstone specimens. Finally, the water imbibition in rock was quantified with the diffusion equation, which was applied to determine the diffusivity of rock when the quantitated water distribution was matched to the observed wetted ring in the laboratory. This study quantifies the evolution of unsaturated moisture distribution in sandstone with soaking time and the variation of uniaxial compression strength as it is affected by the water distribution. The results from this study can be used as the scientific bases to study the rock weakening mechanism in a water environment.